A New Model for three-dimensional Deformation Extraction with Single-track InSAR Based on Mining Subsidence Characteristics - Hongdong Fan; Liang Wang; Binfan Wen; Sen Du (International Journal of Applied Earth Observations and Geoinformation, 2021)
This paper presents a new model for three-dimensional deformation extraction of single-track interferometric synthetic aperture radar (InSAR) based on mining subsidence characteristics. The model is applied to address the problem of difficult-to-obtain three-dimensional surface deformations in a mining area with high-precision using single-track InSAR. In horizontal or near horizontal coal seam mining regions, land subsidence and horizontal movement are symmetrically distributed along the strike and dip directions of the working face. The proposed method uses this characteristic to calculate the three-dimensional component of surface deformation for the mining area by performing simple addition and subtraction operations on the line-of-sight (LOS) displacement of the symmetric points. Simulations using the developed model show that the root mean square error (RMSE) of the three-dimensional deformations in the vertical, east-west, and north-south directions are 6.9, 5.5 and 8.9 mm, respectively. Experiments were processed using the Sentinel-1A images, and the results show that the vertical displacement generated by the model is consistent with the leveling data. Based on the simulation analysis, it is found that this model can solve the three-dimensional mining deformations, for situations where the strike angle of the coal seam is not perpendicular to the satellite heading.